Radar signal analysis and processing using MATLAB - Mahafza, Bassem R. (CRC Press, 2009)
Offering radar-related software for the analysis and design of radar waveform and signal processing, this book provides comprehensive coverage of radar signals and signal processing techniques and algorithms. It contains numerous graphical plots, common radar-related functions, table format outputs, and end-of-chapter problems.